Management Of Various Socio-Economic Factors Under The United Nations Sustainable Development Agenda - Nassani, Abdelmohsen A.; Qureshi, Muhammad Imran; Qayyum, Shazia; Aldakhil, Abdullah Mohammed; Qazi Abro, Muhammad Moinuddin; Zaman, Khalid (Elsevier Ltd, 2019)
The objective of the study is to assess the United Nation's healthcare sustainable development agenda by controlling the number of socio-economic and environmental factors, including carbon emissions, particulate emission damages, natural resource depletion, communicable diseases, and per capita income in a panel of 40 Sub-Saharan African (SSA) countries. The study covered a time period of 2000–2016 for robust inferences. The pooled Mean Group (PMG) estimator is used to controlled possible heterogeneity and cross-sectional dependence. The results confirmed the inverted U-shaped relationship between per capita income and natural resource depletion, while the U-shaped relationship is found between communicable disease and per capita income. The long-run results confirmed that communicable diseases and particulate emission damages both negatively linked with the country's per capita income, while there is a direct association between per capita income and carbon emissions across countries. The results further reveal that particulate emission damages and high mass carbon emissions largely associated with the communicable diseases that need sustainable healthcare policies to delimit carbon-particulate emissions growth in a panel of SSA countries. The undeniable health losses and low adaptability of environmental sustainability reforms lag behind the SSA countries from the assigned target of United Nation's sustainable development goals, which need national and international collaborations to designed better healthcare policies to prevent from infectious diseases that lead towards sustained global healthcare infrastructure.